1997
DOI: 10.1109/50.580819
|View full text |Cite
|
Sign up to set email alerts
|

Devitrification in annealed optical fiber

Abstract: Abstract-The decrease in transmittance of annealed optical fiber has been measured versus temperature and time. The annealing loss is due to the devitrification of the glass and OH absorption in the 1200 to 1500 nm wavelength region. Both loss mechanisms propagate primarily from the surface into the core. However, to increase the OH absorption significantly, annealing times greater than 10 h are required. Fibers heated from 1000 to 1300 C in an air atmosphere quickly devitrify and their transmittance approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The reflection mode is even more attracting because the signal to noise ratio is much bigger and it allows cancelling partly the reciprocal effects such as the linear birefringence. The Verdet constant complies with the physical value given at 0.6% accuracy by [8]. Very small deviations of about 0.72% in the long term have been observed in reflection mode.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The reflection mode is even more attracting because the signal to noise ratio is much bigger and it allows cancelling partly the reciprocal effects such as the linear birefringence. The Verdet constant complies with the physical value given at 0.6% accuracy by [8]. Very small deviations of about 0.72% in the long term have been observed in reflection mode.…”
Section: Resultssupporting
confidence: 53%
“…The Verdet constant of the 3 types of fiber is similar of the order of 0.7 rad/MA which is close to the expected value at = 1550 nm [8]. On the other hand, the standard deviation of the linear birefringence can vary widely underlying the influence of the external perturbation (temperature and vibration) without affecting the determination of the Verdet constant.…”
Section: Analysis Of the Tore Supra Measurementsmentioning
confidence: 81%
See 2 more Smart Citations
“…The spectral shape does not change though the optical intensities of the peaks become large. It is reported that the OH in optical fiber is influenced by the experimental atmosphere [7]. Thus, it is considered that the amount of OH, which is the origin of the peaks, increased during heat treatment at 1000°C in the air.…”
Section: Resultsmentioning
confidence: 98%